Integration of Al-Kindi's Rationalism and Ar-Razi's Empiricism: The Relevance of Islamic Epistemology for Contemporary Science - Cardasyifa Fajranada Usman; Widiya Tasa; Muhammad Emil Fauzi; Rostanura Aji (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The decline of scientific tradition in the contemporary Islamic world indicates an epistemological disconnect between the classical scientific heritage and the development of modern science. The current educational paradigm tends to be imitative and separated from the spiritual, rational, and empirical values that once served as the foundation of Islamic scientific glory. This study aims to analyze the thoughts of Al-Kindi and Ar-Razi as two central figures representing rationalism and empiricism in the classical Islamic scientific tradition. The approach used is a qualitative literature study method using primary data in the form of books and articles adopted from the works of both figures and supporting secondary data in the form of books on Islamic intellectual history, studies of the philosophy of science, and scientific articles. The results show that Al-Kindi developed deductive rationalism that combines reason and revelation, while Ar-Razi emphasized inductive empiricism based on observation and experimentation. The synthesis of these two approaches forms an epistemological framework that balances theoretical reasoning and empirical verification, which then becomes the basis of the modern scientific method. This study emphasizes the importance of re-internalizing the critical spirit, intellectual autonomy, and orientation towards the welfare of the people in reviving the scientific tradition in the Islamic world, while contributing to contemporary Islamic philosophy by offering a model of epistemological integration relevant to education and research.